Prenatal genetic diagnosis of retinoblastoma in two Vietnamese families - Minh Chau, Pham Thi; Hong Anh, Trinh; Lan Anh, Luong Thi; Thuy Duong, Nguyen; Hai Ha, Nguyen (Vietnam Journal of Biotechnology, 2022)
Retinoblastoma (Rb) is a rare cancer that develops from the layer of cells in the retina. A germline mutation in the RB1 gene is a high risk factor for Rb. We performed prenatal genetic diagnosis on two pregnant women who had had a child with hereditary Rb and continued checking their newborns' conditions after giving birth. Ultrasound-guided amniocentesis, amniotic cell culture, and Sanger sequencing for the specific RB1 region were used. The analysis results demonstrated that one of the amniotic cell samples was found to carry a genetic mutation that causes the disease, inherited from the father. Neonatal screening confirmed that the corresponding newborn of the amniotic cell sample with the causative gene mutation developed binocular retinoblastoma. Prenatal genetic testing on pregnant women in families with a risk of having a child with retinoblastoma should be performed to prepare a clinical diagnosis and treatment plan for the neonate.